Pectin production using emerging green extraction technologies: Systematic review - Paucarchuco Soto, Joselin (2025)
Pectin is a versatile biopolymer, which possesses a dual property of strength and flexibility, and can be extracted from various organic sources following green methodologies. The objective of the present review was to identify the emerging green extraction technologies used to obtain pectin, as well as to analyze the extraction yield rate and the appropriate operating parameters to obtain pectins with better rheological characteristics. The databases (Scopus, Scielo and Science Direct) were used, following the PRISMA guidelines and the PIO strategy (Population, Intervention, Outputs), which facilitated the formulation of the search equations and the identification of the most relevant articles of the last 5 years. Through bibliometric analysis, the most promising technologies for obtaining pectin were identified as ultrasound; ohmic heating; supercritical CO2; pulsed electric field; high pressure processing; radiofrequency; microwaves and subcritical water, which are green technologies that offer pectins with degrees of esterification higher than 50%, classifying them as high in methoxyl. In conclusion, innovative technologies promote more environmentally friendly extraction compared to traditional methods, as they involve lower energy consumption and reduce the use of toxic solvents.